Selective methanation of CO in H2-rich gas using Pd/TiO2, Ni/TiO2 and PdNi/TiO2 catalysts - Mtemeli, Patronella Siphatisiwe (Department of Chemical Engineering, 2025)
Hydrogen fuel cells are renowned for their ability to produce minimal or negligible levels of harmful greenhouse emissions, making them pivotal in mitigating climate change. Hydrogen is a versatile energy carrier that can replace petroleum in various energy applications. During hydrogen production, the reformate gas contains a significant amount of carbon monoxide, about 10-60%, which is reduced to about <1% by a two-stage water gas shift reaction. To optimise the performance of fuel cells, it is imperative to reduce CO levels to below 10 ppm, as higher concentrations can compromise the electrochemical functionality of platinum anodes. Therefore, there exists a need to develop an efficient and cost-effective catalyst with a wide temperature window for CO-SMET to reduce the concentration of CO to the desired concentration. This study reports the synthesis of Pd/TiO2, Ni/TiO2 and PdNi/TiO2 catalysts for CO-SMET in H2 gas through wet impregnation and polyol methods. The structural characterisation of the catalys